Good Corporate Governance, Profitability, and Sustainability Report Disclosure: The Moderating Role of Firm Size - Nesya Aqillah Santoso; Frido Simatupang (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Over time, companies are required to be more than just profit-oriented, but also responsible for people and the planet, in accordance with the "Triple-P Bottom Line" concept, which serves as a reference for companies in disclosing sustainability reports. This study aims to analyze the influence of independent boards of commissioners, audit committees, and return on assets on sustainability report disclosure, with firm size as a moderating variable, in energy sector companies listed on the Indonesia Stock Exchange (IDX) for the 2022-2024 period. Using the purposive sampling technique, a sample of 22 companies was obtained. Data analysis was conducted using the panel data regression method and Moderated Regression Analysis (MRA) processed using E-views 13. The results of the study indicate that the independent board of commissioners, audit committee, and return on assets do not partially influence the disclosure of sustainability reports. Firm size can moderate the influence of the independent board of commissioners and return on assets on sustainability report disclosure. Meanwhile, firm size cannot moderate the influence of the audit committee on sustainability report disclosure. These results contribute to the sustainability reporting literature by highlighting the conditional role of firm size in strengthening governance and profitability mechanisms, particularly within the energy sector of an emerging market context.